Nutrigenomics: Understanding the Connection Between Nutrition and Genetics - Saputra, I Putu Gede Windhu (Bali Medical and Wellness Journal, 2024)
Nutrigenomics is a field that combines "nutrition" and "genomics." It focuses on how nutrients, both micronutrients and macronutrients, affect our genome. This includes understanding how nutrients interact with genes during transcription and gene expression, leading to varying responses based on different gene variants. One significant factor in this process is Transcription Factors (TFs), which are crucial for how nutrients influence gene activity. Several diseases, including cancer, diabetes, cardiovascular diseases, and dyslipidaemia, are linked to diet and nutrition. From a nutrigenomics perspective, conditions like diabetes and obesity often stem from an imbalanced diet that interacts with active genes. In daily life, nutrigenomics helps assess individual nutritional needs based on a person's genetic profile, which is sometimes referred to as personalized diet. This approach aims to prevent chronic diseases over time. However, nutrigenomics also raises ethical concerns, particularly regarding the privacy of individuals' genetic information and the need for further research in this area.